PANAMBI: UMA BREVE ANÁLISE SOCIOECONÔMICA - Eduardo Rafael Dos Santos Malheiros, Eduardo Rafael Dos Santos Malheiros Eduardo Rafael Dos Santos Malheiros; Dyllan Frees, Dyllan Frees; Vinicio Gollin De Sena, Vinicio Gollin De Sena Vinicio Gollin De Sena; Rayan Rossi Bonadiman, Rayan Rossi Bonadiman Rayan Rossi Bonadiman; Dilson Trennepohl, Dilson Trennepohl (Salão do Conhecimento, 2017)
Estudo realizado no âmbito do Progama de Educação Tutorial - PET Economia da UNIJUI